Parenting a child with Asperger syndrome : 200 tips and strategies - Boyd, Brenda (Jessica Kingsley, 2003)
'This book is brilliant. I've read it through, re-read sections and still want to pick it up and dip into it. The approach is very refreshing - easy to read, practical and realistic ... So many parents are going to breathe a sigh of relief when they read this book.'. - Julie Connell, Educational Psychologist. For parents of children with Asperger Syndrome ordinary parenting just doesn't always do it - AS kids need a different approach. Brenda is mother to thirteen-year-old Kenneth, author of Asperger Syndrome, the Universe and Everything, and since his diagnosis at the age of eight she has gath.